Tunable Bandpass Filters With Co-Integrated Isolator and Switching-Off Functionality - Kexin Li; Dimitra Psychogiou (IEEE Journal of Microwaves)
This paper reports on a new type of multi-functional bandpass filtering (BPF) architecture with center frequency tunability, switching-off, and isolator functionality. The proposed filter, isolator, and switch (FIS) combines frequency-tunable passive resonators with unilateral frequency-selective stages (UFSs) to achieve tunable, fully-directional, quasi-elliptic transfer functions. The UFS, consists of a transistor-based path and a tunable feedback network, enabling frequency-selective transmission in the forward direction, RF signal cancellation in the reverse direction, and reconfigurability in terms of center frequency and intrinsic switching-off. It is demonstrated that by cascading UFSs and tunable resonators, highly selective frequency-tunable FISs can be developed. The proposed FIS also offers a reconfigurable switch-off mode capability with high isolation that is obtained by adjusting transmission zeros and reconfiguring the UFSs. In this paper, two types of UFSs are analyzed using circuit schematic simulations and coupling routing diagram (CRD)-based synthesis. Scalability to high-order transfer functions is also demonstrated by CRD-synthesized examples, design examples and manufactured prototypes. For experimental validation, two tunable UFSs and four tunable FISs were manufactured and measured at the L band.